Effect of infection with Cucumber mosaic virus on some physiological indicators and productivity of several hybrids of pepper. - العجورية, حلا; إسماعيل, عماد; سمرة, بديع; صهيوني, فهد (Latakia University Journal -Biological Sciences Series, 2022)
A study was conducted at Al-Muturki village in Lattakia Governorate during 2019/2020 growing season to investigate the effect Cucumber mosaic virus (CMV) infection on some physiological indicators (relative water content (%RWC), proline production and hydrogen peroxide production) and weight and number of fruits of four pepper hybrids (Taline F1, Amani F1, Harek F1 and Marvilo F1) at three periods post viral inoculation (15, 30 and 45 days). The experiment was carried out by using complete randomized block design with 8 treatments and 4 replicates per treatment. The results showed that the viral infection affected the studied indicators 15 days after virus inoculation.The highest effect of the viral infection was at 30 days after virus inoculation, The effect of infection with the virus represented a decrease in the relative water content and weight and number of fruits and an increase in the values ​​of proline and hydrogen peroxide in the hybrids of pepper infected with the virus with significant differences compared to the control plants. However, 45 days after virus inoculation, the effect of viral infection decreased with plant age.